2008
DOI: 10.1007/s12149-008-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of renal handling and uptake of two somatostatin receptor-specific peptides labeled with indium-111

Abstract: Both in vitro methods showed a higher renal accumulation of (111)In-DOTA-NOC in comparison with (111)In-DOTA-TATE. The renal uptake was partly decreased by inhibitors of receptor-mediated endocytosis and by a block of energy-dependent processes. A significant participation of active transport processes in renal accumulation of the studied peptides was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Several ligands have been reported to bind both to megalin and to cubilin (8). In vitro studies have indicated that radiolabeled somatostatin analogs are actively reabsorbed in proximal tubular cells by receptor-mediated endocytosis, probably involving megalin or cubilin (11). Autoradiography studies of rodent kidneys showed that various radiolabeled peptides accumulate mainly in the renal cortex (12).…”
Section: Proximal Tubular Reabsorption and Processingmentioning
confidence: 99%
“…Several ligands have been reported to bind both to megalin and to cubilin (8). In vitro studies have indicated that radiolabeled somatostatin analogs are actively reabsorbed in proximal tubular cells by receptor-mediated endocytosis, probably involving megalin or cubilin (11). Autoradiography studies of rodent kidneys showed that various radiolabeled peptides accumulate mainly in the renal cortex (12).…”
Section: Proximal Tubular Reabsorption and Processingmentioning
confidence: 99%
“…Ligands with carboxyl groups on dangling chains are normally evaluated in renal tracer development because the interaction of the renal receptor with the carboxyl group is important for clearance of small peptides 14-16. Tridentate ligands being investigated in bioconjugates or in tracers often have the dangling group attached to a central N anchoring the two chelate rings 10,17-19.…”
Section: Introductionmentioning
confidence: 99%
“…The time of the renal half-excretion of protein correlates with the molecular size: the limit of glomerular filtration is estimated at 60-65 kDa [15]. The full-size IgG molecules (~150 kDa) (Fig.…”
Section: Truncated Antibody Fragments and Alternative Framework Prmentioning
confidence: 97%